Analysis of Meaning With A Mimesis Approach of The Poem "Memecah Mengutukan" By Emha. Ainun N. - Ahmad Maskur Subaweh; Ade Hasanudin (Journal of General Education and Humanities, 2026)
The background of this research is due to the need for a deep understanding of the poem "Memecah dan Mengutuhkan" by MH. Ainun N as part of the reflection of today's social life. The purpose of this research is to understand the meaning of the poem with a mimetic approach from the poem "Putus Desa" by MH. Ainun N. The descriptive qualitative research method is the method used in this research. The poem "Memecah dan Mengutuhkan" by MH. Ainun N is the data subject, which consists of words and sentences whose meanings are analysed using a mimetic approach. The data collection technique is carried out in the following stages: (1) reading the poem "Memecah dan Mengutuhkan" by MH. Ainun N; (2) collecting words, sentences, or quotes to be analysed; (3) using a mimetic approach, the data is then analysed; (4) presenting the results of the analysis in descriptive form. The results of this research are that this poem reflects several reflections on the current human situation, where people pay less attention to their spiritual life. People are so busy with their work that their emotions are drained, depicting a society that prioritises ego and lust, which can sometimes be the root of problems in one's life. The human ego is sometimes too high to achieve goals and objectives, so one must strive to exceed its limits. In conclusion, this poem serves as a mirror for its readers to evaluate themselves regarding bad habits in viewing life that are not too materialistic, and do not sacrifice the spiritual side.